2017
DOI: 10.1007/s00244-017-0401-1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Distributions of Air Pollutants and Size Distribution of Aerosols over Central and Eastern China

Abstract: The origins and spatial and temporal distributions of air pollutants (PM, PM, CO, SO, NO and O) during May to June of 2015 were investigated using data from 1490 monitoring sites in China. Aerosol number concentrations and meteorological data from Shijiazhuang, Nanjing, and Suzhou were combined with the MIX Asian emission data and the HYSPLIT model. Furthermore, the diurnal variation, size distribution, and main sources of air pollutants and aerosols were selectively characterized in the North China Plain (NCP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…In order to compare, we present typical results in other parts of the world, in particular in Eastern-Central China. The mean results obtained by Wang et al [13] are the followings: 12,661, 11,189 and 12,797 particles/cm 3 for Shijiazhuang, Nanjing and Suzhou, respectively.…”
Section: Ground Measurements With Aerosol Spectrometer At Leo Sitementioning
confidence: 89%
See 1 more Smart Citation
“…In order to compare, we present typical results in other parts of the world, in particular in Eastern-Central China. The mean results obtained by Wang et al [13] are the followings: 12,661, 11,189 and 12,797 particles/cm 3 for Shijiazhuang, Nanjing and Suzhou, respectively.…”
Section: Ground Measurements With Aerosol Spectrometer At Leo Sitementioning
confidence: 89%
“…Other implications of SO2 and sulfate aerosol propagations for the air quality as well as for possible environmental and economical consequences have been described in the works of Yeh et al [13] and Wang et al [14].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Many studies have investigated the aerosol mass concentrations and optical properties in the YRD. [4,5] Ming et al reported distinctive seasonal trends of the PM 2.5 concentrations in the YRD. [6] That is, the PM 2.5 concentrations in the YRD are higher in winter and lower in summer.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–3 ] Many studies have investigated the aerosol mass concentrations and optical properties in the YRD. [ 4,5 ] Ming et al. reported distinctive seasonal trends of the PM 2.5 concentrations in the YRD.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the pollution situation of the air environment in the YRMR is becoming increasingly serious [22][23][24]. As we know, regional haze pollution is closely related to the meteorological conditions, geographical location (e.g., the proximity to a sea or lake), terrain, economic development, and human population [1,[25][26][27]. The sources of aerosol over the THB, are comprised of primary and secondary aerosols from local and surrounding areas and are intricate due to the dense emission sources of ships, traffic, and agriculture, and complex meteorological conditions [24].…”
Section: Introductionmentioning
confidence: 99%